Efficient and Highly Selective Solvent‐Free Oxidation of Primary Alcohols to Aldehydes Using Bucky Nanodiamond. Issue 17 (18th August 2017) - Lin, Yangming; Wu, Kuang‐Hsu (Tim); Yu, Linhui; Heumann, Saskia; Su, Dang Sheng
Abstract: Selective oxidation of alcohols to aldehydes is widely applicable to the synthesis of various green chemicals. The poor chemoselectivity for complicated primary aldehydes over state‐of‐the‐art metal‐free or metal‐based catalysts represents a major obstacle for industrial application. Bucky nanodiamond is a potential green catalyst that exhibits excellent chemoselectivity and cycling stability for the selective oxidation of primary alcohols in diverse structures (22 examples, including aromatic, substituted aromatic, unsaturated, heterocyclic, and linear chain alcohols) to their corresponding aldehydes. The results are comparable to reported transition‐metal catalysts including conventional Pt/C and Ru/C catalysts for certain substrates under solvent‐free conditions. The possible activation process of the oxidant and substrates by the surface oxygen groups and defect species are revealed with model catalysts, ex situ electrochemical measurements, and ex situ attenuated total reflectance. The zigzag edges of sp 2 carbon planes are shown to play a key role in these reactions. Abstract : Bucky star : An effective catalytic reaction pathway for the selective oxidation of primary alcohols with various functionalities and structures has been developed with bucky nanodiamond as a catalyst. The zigzag edges of sp 2 carbon planes play a crucial role in these reactions.